2022
DOI: 10.3390/medicina58101393
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Changes in Fatigue-Related Symptoms Due to Long COVID: A Single-Center Retrospective Observational Study in Japan

Abstract: Background and Objectives: Changes in post COVID-19 condition (PCC) characteristics caused by viral variants have yet to be clarified. We aimed to characterize the differences between clinical backgrounds and manifestations in long COVID patients who were infected with the Delta variant and those who were infected with the Omicron variants. Materials and Methods: This study was a single-center retrospective observational study for patients who visited our COVID-19 aftercare outpatient clinic (CAC) established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
(39 reference statements)
0
14
0
1
Order By: Relevance
“…At the beginning of the year 2022, the Omicron variant became the predominant cause of the disease [ 130 ]. Infection with the Omicron variant caused milder disease with much fewer need for hospitalization [ 131 , 132 ]. There were less frequent lower respiratory tract infections caused by the Omicron variant and thus less frequent severe forms of the disease were observed [ 133 ].…”
Section: Continuing Mutation Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…At the beginning of the year 2022, the Omicron variant became the predominant cause of the disease [ 130 ]. Infection with the Omicron variant caused milder disease with much fewer need for hospitalization [ 131 , 132 ]. There were less frequent lower respiratory tract infections caused by the Omicron variant and thus less frequent severe forms of the disease were observed [ 133 ].…”
Section: Continuing Mutation Of Sars-cov-2mentioning
confidence: 99%
“…In addition, the probability of symptoms persisting beyond two months in the patients infected with the Omicron variant appeared to be diminished as compared with ancestral COVID-19 [ 134 , 135 ]. Long-COVID symptoms in the patients infected in the period of the Omicron variant predominance differed from the symptoms in the patients infected in the period of predominant Delta variant, with a higher incidence of cough (20% vs. 7%), fatigue and insomnia, and lower incidence of dysosmia and dysgeusia [ 131 ].…”
Section: Continuing Mutation Of Sars-cov-2mentioning
confidence: 99%
“…According to our epidemiological classification of COVID-19 in Okayama Prefecture in Japan, [ 12 ] we divided the patients’ onset of COVID-19 into three groups: the Preceding phase is the period from the ancestral variant to the Alpha variant, before 18 July 2021; the Delta variant phase is the period from 19 July 2021 to 31 December 2021, when the Delta variant was dominant after the Alpha variant phase; and the Omicron variant phase is the period after 1 January 2022, when the Omicron variant was dominant in Okayama Prefecture [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The presence of "brain fog" symptoms was carefully determined by individual interview, based on complaints of the subjective feeling of concentration difficulty and impaired ability to concentrate and/or think; namely, being mentally slow, fuzzy, or spaced out, affecting the patient's ability to think or concentrate with a dull headache [16]. The onset of COVID-19 in the patients was divided into three groups based on the epidemiological aspects of COVID-19 in Okayama Prefecture in Japan: preceding period; Delta-dominant period; and Omicron-dominant period [11]. The preceding period is the period from the ancestral strain to the Alpha strain, before 18 July 2021; the Delta-dominant period is the period from 19 July 2021 to 31 December 2021, when the Delta variants were dominant after the Alpha-dominant phase; and the Omicron-dominant period is the period after 1 January 2022, when the Omicron variants were dominant in Okayama Prefecture, Japan.…”
Section: Study Design and Inclusion Of Patientsmentioning
confidence: 99%
“…It was found that the major complaints in the early period of the COVID-19 pandemic were fatigue and anxiety [9] and that the severity of the infection status affected the number and duration of persistent symptoms [10]. The frequency of each symptom of long COVID has been changing with the emergence of new variants of SARS-CoV-2 [11]. Moreover, we have shown that endocrine factors including anterior pituitary, adrenal and thyroid hormones [12], and male androgen levels [13,14] might be related to the fatigue symptoms of long COVID.…”
Section: Introductionmentioning
confidence: 99%